2021
DOI: 10.56027/joasd.spiss082021
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of responses among Medicago truncatula lines to Phoma medicaginis infection.

Abstract: Medicago truncatula is an omni-Mediterranean species grown as an annual forage legume. In addition to its small genome size and simple genetics, M. truncatula harbors several attributes, which make it an attractive model forage plant. In this study, we investigated the variation of responses in ten parental lines of M. truncatula to Phoma medicaginis infection. Plants were cultivated in the growth chamber under controlled conditions and were inoculated after two months with P. medicaginis. At harvest, 13 quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, the study of the diversity of responses in 10 parental lines of M. truncatula to infection by Phoma medicaginis revealed that the tolerant lines are those with the lowest ratios of number of infected and dead leaves [31]. The studied lines constitute three groups according to their responses to infection with P. medicaginis.…”
Section: Adaptation To Abiotic and Biotic Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the study of the diversity of responses in 10 parental lines of M. truncatula to infection by Phoma medicaginis revealed that the tolerant lines are those with the lowest ratios of number of infected and dead leaves [31]. The studied lines constitute three groups according to their responses to infection with P. medicaginis.…”
Section: Adaptation To Abiotic and Biotic Constraintsmentioning
confidence: 99%
“…Finally, Medicago species showed a high level of variability in responses to abiotic and biotic stresses. Diversity within and among populations has been noted for water deficit [24], salinity [25][26][27], nutritional deficiencies [28], and resistance to pathogens [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its significance as a forage legume, there has been limited work on varietal selection for this species in Tunisia, with only two registered local varieties (Gabès and El Hamma) ( Jabri et al., 2021 ; Maiza et al., 2021 ). Therefore, it is advisable to initiate new varietal selection efforts for alfalfa, utilizing diverse germplasm, to develop new varieties with robust agronomic performance under the combined constraints of salinity and P. medicaginis infection in the context of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Like many other regions globally, it faces the challenge of climate change and its associated environmental stresses, among which soil salinization and pathogen infections are particularly important for alfalfa productivity (Djebali, 2008;Arraouadi et al, 2011;Badri et al, 2021). Furthermore, the interaction between salinity and Phoma medicaginis infection can exacerbate the adverse effects of these stresses on alfalfa plants (Castell-Miller et al, 2007;Kaiwen et al, 2020;Maiza et al, 2021). The coexistence of these stresses creates a more hostile environment for the crop to thrive.…”
Section: Introductionmentioning
confidence: 99%